A Measure of the Quality of Educational Leadership Programs for Social Justice: Integrating LGBTIQ Identities Into Principal Preparation. (April 2015) - O'Malley, Michael P.; Capper, Colleen A.
Purpose: The purpose of this study is to investigate how aspiring principals in the United States are prepared for social justice leadership, by focusing particular attention on equitable leadership for lesbian, gay, bisexual, transgender, intersex, and questioning (LGBTIQ) persons as a measure of the preparation program's commitment to social justice.Research Method: The research design involved a cross-sectional survey instrument completed by 218 full-time faculty teaching in 53 different University Council for Educational Administration university principal preparation programs. We performed descriptive analysis of Likert-type scale responses with cross-tabulation of selected survey questions and constant comparative analysis of open-ended questions. The descriptive analysis provides a one-moment-in-time snapshot of the perceptions of particular education leadership faculty. As such, the data are illustrative of certain patterns evident across the national sample rather than definitive of these programs.Findings : Findings indicate that LGBTIQ identities and themes are only marginally integrated into U.S. principal preparation programs, inclusive of those identified as social justice programs. Social justice programs that do address LGBTIQ identities frequently depend on one faculty member or course to do so, rather than being integrated throughout the program.Implications for Research and Practice: Strategies are clearly needed for integrating LGBTIQ equitable leadership into U.S. principal preparation. More fundamentally, the study challenges the manner in which social justice discourses are constructed. It suggests that the quality of social justice preparation is appropriately measured, in part, and enhanced by the form of communal engagement with identities and experiences marginal within the social justice discourse itself.